2014
DOI: 10.1159/000369393
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fat Mass Measured by Dual-Energy X-Ray Absorptiometry and Leptin in Preterm Infants between Term Age and 6 Months' Corrected Age

Abstract: Background/Aims: In term subjects, fat mass (FM) is positively associated with leptin, whereas studies in preterm infants show conflicting results. However, none of these studies measured FM by dual-energy X-ray absorptiometry (DEXA). This study aims to relate FM measured by DEXA in relation to leptin and growth in preterm infants. Methods: In 139 preterm infants, weight (kg) and length (cm) were measured at birth, term age, and 6 months' corrected age (CA). FM (kg), measured by whole-body DEXA, and leptin (µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This is supported by van Poelje et al (21) who identified that weight z -scores gain from term to 6 months CA resulted in higher fat mass and higher leptin concentrations at 6 months CA, indicating that leptin is a marker of body fat mass during the first 6 months after term. Bozzola et al (17) identified higher leptin concentrations in AGA versus SGA term born infants at birth and comparable levels at 1st, 6th and 12th month of age.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This is supported by van Poelje et al (21) who identified that weight z -scores gain from term to 6 months CA resulted in higher fat mass and higher leptin concentrations at 6 months CA, indicating that leptin is a marker of body fat mass during the first 6 months after term. Bozzola et al (17) identified higher leptin concentrations in AGA versus SGA term born infants at birth and comparable levels at 1st, 6th and 12th month of age.…”
Section: Discussionsupporting
confidence: 52%
“…In term infants, leptin levels correlate positively with birth weight, gain in fat mass, and body mass index (BMI) (17, 21). Leptin levels increase after birth until 6 months, but showed a trend to return to birth levels by 1 year of age (17).…”
mentioning
confidence: 99%
“…In term‐born children at school age, leptin has also been positively associated with FM index (ie FM adjusted for height) . We showed that this association was also present in preterm‐born children at term age and 6‐month corrected age (CA, ie calculated from term age) …”
Section: Introductionmentioning
confidence: 62%
“…Decreased levels of IGF‐1 in early postnatal life have been associated with neonatal morbidities such as bronchopulmonary dysplasia and retinopathy of prematurity, as well as with impaired growth, adverse neurodevelopment and unfavourable body composition . We previously showed that leptin was associated with FM and weight gain between term age and 6‐month CA, and that IGF‐1, together with insulin, was suggested to be involved in the regulation of growth during infancy…”
Section: Discussionmentioning
confidence: 99%
“…Like adiponectin, lower leptin levels were detected in premature infants at birth, with greater decreases in relation to lower GA [46]. However, this correlation may become inverted when levels are analyzed at later ages, probably influenced by the growth pattern and an increase in BMI [53] and the amount of fat mass [54]. In line with these statements, some studies demonstrated that a rapid weight catch-up in early infancy, often detected in premature and SGA children, may affect both, the degree of adiposity and the IR, as well as leptin concentrations [55].…”
Section: Discussionmentioning
confidence: 94%